Efektivitas Workshop Online Pengajaran Bahasa Inggris untuk Anak di Masa Pandemi Covid-19 - Amalia, Arsyi Rizqia; Irene Evi Krismawati (FKIP Universitas Muhammadiyah Sukabumi, 2021)
During the Covid-19 pandemic, there a lot of online events that are held to share education for everyone included for teacher, students, parents or education practitioners. One of the events is online workshop for teaching English, and this study will be focused in online workshops of teaching English for young learners. Research methodology in this study was descriptive comparative. In this study, author will compare two online workshops, with initial name: Workshop A and Workshop B. The data collection in this study gain from: planning, implementation, and evaluation activities. From planning activities, workshop A and B have similarities in determining themes, target audience/participant, workshop procedure and socialization of the event. Workshop A and B have differences in the selection of sub-themes and the number of event committees, speakers, and registrant (workshop B have more number of committees and speakers). In the implementation, the number of participants in workshop A was less than in workshop B, but the mentoring activities in workshop A were more focused and active. In the evaluation activity, the results of the projects in workshop A were better than workshop B. Based on the overall evaluation, both workshop A and workshop B obtained participants according to the target, while the shortcomings that were very visible in these two workshops were the large number of participants who did not complete the task according to the target achievement. Based on these findings, future workshop organizers can make a better plan workshop designs to avoid finding workshop problems that have been described in this paper.